الاسرى الفلسطنيين بين مطرقة السجان وسندان التشريعات الاسرائيلية - أحمد صلاح, عقل محمد (University of Eloued جامعة الوادي, 2020)
هدفت هذه الدراسة إلى تسليط الضوء على سلسلة القرارات التي تم سنها في الكنيست الإسرائيلي ومدى تأثيرها على الأسرى، ودور إدارة مصلحة السجون في تنفيذ هذه القوانين والإجراءات التي تضيق على الأسرى وتسلبهم حقوقهم. وتناولت الدراسة الموقف الفلسطيني الرسمي والشعبي الذي لم يتعد التهديد والشجب والاستنكار، حيث لم تتخذ السلطة أي قرار يمنع إسرائيل من الاستمرار في تنفيذ القوانين، وكل التهديدات بقيت حبرًا على ورق. وفي المقابل، نفذت إسرائيل كل ماتم سنه من قبل الكنيست، حيث تمحورت السياسة الإسرائيلية حول معاقبة الأسرى واستهدافهم بكل الوسائل والسبل، وتفننت بأساليب تعذيب الأسرى في مركز تحقيق المسكوبية في نهاية سنة 2019. This study aimed to shed light on the series of decisions enacted in the Israeli Knesset and the extent of their impact on prisoners and the role of the Prison Authority Administration in implementing these laws and procedures that besieging the prisoners and deprive them of their rights. The study also dealt with the official and popular Palestinian stance, which did not exceed threat, denunciation and condemnation. Where the Palestinian Authority has not taken any decision to prevent Israel from continuing the implementation of laws, and all threats remained a dead letter. On the other hand, Israel has implemented every law enacted by the Knesset, as the Israeli policy focused on punishing and targeting prisoners by all means and ways and it mastered methods of torturing prisoners at almaskubia investigation center at the end of 2019.
مجلد 11، عدد2
Keywords: مصلحة السجون الإسرائيلية، الكنيست، القرارات الإسرائيلية، الحركة الأسيرة، السلطة الفلسطينية، تعذيب الأسرى.; Israeli Prison Service, The Knesset, Israeli decisions, Captive movement, Palestinian Authority, Torture of prisoners